Micro End Milling Polystyrene for Microfluidic Applications - Christ, Kevin T.; Smith, Bryce B.; Pfefferkorn, Frank E.; Turner, Kevin T. (5th International Conference on MicroManufacturing (ICOMM 2010), 2010)
Microfluidic devices developed in research labs are often fabricated from poly(dimethylsiloxane) (PDMS) because techniques to manufacture devices via lithographic and molding techniques are well-established. However, thermo-plastics have more desirable properties for many applica-tions and are typically used for mass-produced polymer mi-crofluidic devices. Therefore, there is a critical need for techniques to rapidly prototype thermoplastic devices in re-search and development labs. Here we investigate the micro end milling of polystyrene and demonstrate microfluidic de-vices fabricated using this process. A parametric study was undertaken in order to assess the effects of tool speed, feed rate, and depth of cut on finished channel width, bottom surface roughness, and burring along the channel sides. It was found that low cutting depths and high feed rates pro-duce the best channels. Straight microfluidic channels with graded and stepped bottom geometries were fabricated and tested. In addition, a microfluidic diffusive gradient device was fabricated and shown to work. Polystyrene microfluidic devices enable the use of materials that are more comparable to standard tissue culture labware and present a more direct route to commercialization.
Keywords: polystyrene; microfluidics; micro end milling